Accelerating Sales in Start‐Ups: A Domain Planning, Network Reliance, and Resource Complementary Perspective. (1st July 2019) - Marvel, Matthew R.; Sullivan, Diane M.; Wolfe, Marcus T.
Abstract : Business planning is central to entrepreneurship and of immense interest in explaining venture development. This study investigates how planning in different functional domains, and network reliance for domain planning, relate to speed of initial sales success. Drawing from a sample of founders in the high‐technology sector, we find differential planning effects—market planning lengthens the time to sales whereas technology planning reduces time to sales. Further, we find that founders' reliance on network sources of help for market planning, relative to solo planning, simultaneously complements both market and technology planning and reduces time to sales. Our findings illustrate domain planning, network reliance, and resource complementarities as important to venture development.